(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This research aims to design a new kutu kebaya design with Semen Rante batik motif that is adaptive for plus-size women without eliminating the aesthetic and cultural values ​​inherent in traditional Indonesian clothing. The method used is design research which includes the stages of identifying user needs, exploring motifs and design concepts, developing alternative designs, and visualizing the final product. The design was carried out by applying an inclusive design approach that considers aspects of body proportion, comfort, function, and aesthetics. The Semen Rante batik motif was chosen as the main element because it contains philosophical values ​​about life, strength, and attachment that represent Indonesian cultural identity. The design results show that the new kutu kebaya can be developed into a more adaptive clothing for plus-size users through the use of a looser silhouette, the selection of lightweight and comfortable materials, and the application of design details that can give a proportional impression to the body. The resulting design still maintains the characteristics of the traditional kebaya while meeting the functional and aesthetic needs of the user. Thus, this design produces an alternative kebaya design that is more inclusive, comfortable, and relevant to the diversity of Indonesian women’s body shapes